Community Structure And Diversity Of Dragonflies (Odonata) As Bioindications Of Water Quality In Telaga Aqua, Tulungagung District - Abidin, Zainal; Ali, Mukhtar Abdul; Kartikasari, Desi; Nurdianyoto, Indra; Maulana, Muhammad Iqbal; Muslimin, Abdul Irhas Ihwanul; Filayani, Muhammad Iqbal (El-Hayah:Jurnal Biologi, 2025)
Dragonflies also play a role in ecosystems as predators and bioindicators of water quality. The study aims to determine the community structure and diversity of dragonflies in Lake Aqua. The study was conducted in April 2021. Type of qualitative descriptive research, with visual day flying method with 3 observation locations based on vegetation composition and ease of access. Sampling using insect nets, documentation and identification. Based on the results of the study, 10 species of odonata were obtained, including 5 species of dragonflies (Anisoptera) and 5 species of needle dragonflies (Zygoptera). The total number of dragonflies found in 3 locations was 337 individuals from 6 families, including Euphaea variegata, Heliocypha fenestrata, Rhinocypha heterostigma, Vestalis luctuosa, Coeliccia membranipes, Onychogomphus fruhstorferi, Orthetrum glaucum, Orthetrum pruinosum, Orthetrum sabina, and Pantala flavescens. The results of the diversity index (H') showed 2.04 medium categories, the highest abundance was found in the species Euphaea variegata which was valued at 24.9% and the lowest abundance was found in Coeliccia membranipes worth 1.2%. The evenness index of 0.9 is high, the dominance index of 0.2 is low, which means dragonflies have the same opportunity to utilize resources. The calculation of the Family Biotic Index (FBI) to 3 locations of 0.02 is included in the category of very good water quality. The higher the number of dragonflies in the ecosystem, indicating that the ecosystem is still natural and environmental sustainability is maintained. When pollution occurs in the waters, it causes the life cycle of dragonflies to be disrupted and their population to decline.